FinTech: The Changing Future of Finance in India - Udainia, Aishwarya; Dr. Angrish Kumar (South Eastern European Journal of Public Health, 2025)
In India, a country known for its decadent array of history and culture, an exciting evolution is taking place; old and new technologies are coming together and affecting each other. In the middle of this mix of culture and technology, a big trend is starting to show: the fast growth of Financial Technology, also known as FinTech. This fusion of finance and technology is transforming the way people handle their money, bringing about a revolutionary change in the financial landscape. The primary goal of this research study is to deliver a complete examination of the FinTech sector in India, with a primary focus on how digitally capable people accept FinTech services. The paper discusses the changing role of FinTech companies and their integration into India's financial landscape through a conceptual lens. By analyzing existing literature and empirical evidence, the study explores the various opportunities and challenges faced by FinTech firms in the Indian market. Additionally, the paper examines the attitudes of Indian consumers towards FinTech services, highlighting the factors that influence consumer behaviour and preferences in this area. It also looks at the current market trends in the FinTech industry in 2024 and offers insights into its prospects, providing valuable implications for policymakers, industry professionals, and researchers.